A Novel Authentication Mechanism to Prevent Unauthorized Service Access for Mobile Device in Distributed Network - V L, Pavani (International Journal of Interactive Mobile Technologies (iJIM), 2018)
The growth of distributed computer networks (DCN) is simple for the user to share information and computing capabilities with the host. User identification is an essential access control mechanism for the client-server networking architecture. The perception of single sign-on allows a legitimate user to access a different service provider on a DCN using a single session key. Recently, several user identification techniques being proposed for DCN. Unfortunately, the existing proposals cannot maintain user anonymity when the majority of probable attacks. In addition, the further time synchronization mechanism they use can result in widespread overhead costs. To overcome these shortcomings, we propose a novel authentication mechanism to prevent unauthorized service access for a mobile device in distributed networks. The mechanism implements methods to generate securely encrypted keys using RSA algorithm to validate the authentication of user login id and password.  Later, it implements a secure session key generation using DH algorithm which allows accessing the different services without repeating the authentication mechanism. An experimental evaluation was performed to measure execution time overhead for the registration process, an authentication process, session key generation process and Service Request Performance. The comparison results with existing authentication mechanism show an improvisation in all the measures.